2016
DOI: 10.1016/j.ssmph.2016.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Differences in neighborhood social cohesion and aerobic physical activity by Latino subgroup

Abstract: Previous research has examined the role of neighborhood social cohesion in physical activity outcomes; however, less is known about this relationship across Latino subgroups. The purpose of our study was to examine the association between neighborhood social cohesion and aerobic leisure-time physical activity (LTPA) among Latino adults and to determine whether these associations differ by Latino subgroup. We used cross-sectional 2013–2014 National Health Interview Survey (NHIS) data on Latinos originating from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 35 publications
1
28
2
Order By: Relevance
“…There is mixed evidence regarding racial/ethnic differences in the association between neighborhood social cohesion and health (Mulvaney-Day et al, 2007; Murillo et al, 2016; Wong et al, 2018). While some researchers find that the relationship between neighborhood social cohesion and health-related outcomes and behaviors vary by race/ethnicity (Wong et al, 2018; Yi et al, 2016), others find no evidence for racial/ethnic differences in these associations (Echevarria et al, 2008; Olamijuwon et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is mixed evidence regarding racial/ethnic differences in the association between neighborhood social cohesion and health (Mulvaney-Day et al, 2007; Murillo et al, 2016; Wong et al, 2018). While some researchers find that the relationship between neighborhood social cohesion and health-related outcomes and behaviors vary by race/ethnicity (Wong et al, 2018; Yi et al, 2016), others find no evidence for racial/ethnic differences in these associations (Echevarria et al, 2008; Olamijuwon et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Physical activity, education, and acculturation 10 (Murillo, Echeverria, and Vasquez 2016). The IRB has determined that this research does not meet the definition of human subjects research and therefore is excluded from the need for additional review (protocol 998398-1).…”
Section: Datamentioning
confidence: 99%
“…19 However, the 4 items used in our study have been used in previous research to assess neighborhood social cohesion and demonstrated high internal consistency. 22 In our sample, this scale demonstrated excellent internal consistency (Cronbach a ¼ .90). A total neighborhood social cohesion score was created by reverse coding and summing the 4 items.…”
Section: Methodsmentioning
confidence: 59%
“…It has also been suggested that social environmental attributes, including social cohesion (ie, solidarity and connectedness within a group), 19 should be investigated as potential moderators of the built environment 20 and critical for obesity prevention. 21 Social cohesion, a measure of neighborhood environment, has also been shown to be related to physical activity in Latinos 22 and may moderate the relationship between neighborhood walkability and physical activity. Further, physical activity may vary by level of social cohesion in the neighborhood walkability-weight status association.…”
mentioning
confidence: 99%